Pengaruh Ekstrak Etanol Daun Jambu Air (Syzygium aqueum (Burm f.)Alston) terhadap Glukosa Darah, Ureum dan Kreatinin Tikus Putih (Rattus norvegicus) - Joni Tandi (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2017)
Diabetes mellitus with complications of Diabetic Nephropathy become one of the most common cause of end-stage renal failure in the world. Impaired kidney function is measured by Glomerular Filtration Rate (GFR). Where the decline in GFR was followed by increased levels of blood glucose, urea and creatinine. This study aimed to determine whether there is the content of secondary metabolites in leaves of Sizygium aqueum leaf extract, at a dose of extract what impact the blood glucose, urea and creatinine levels of male rats and whether the water extract of guava leaves have an influence on the blood glucose, urea and creatinine white male rats. This study uses a randomized block design with six treatment groups consisting of five test animals. Group I was normal control (CMC Na suspension 0.5%). Group II negative control (streptozotocin 40 mg/kg). positive control group III (suspension glibenclamide). Group IV given guava leaf extract 100 mg/kg BW. V group awarded guava leaf extract 200 mg/kg BW. Group VI given guava leaf extract 300 mg/kg BW. Treatment was given for 28 days and measured levels of blood glucose urea and creatinine on days 0, 7, 14, 21 and 28. The results showed nefroprotektif effect on all groups and most effective extract are a group of guava leaf extract 100 mg/kg BW). Keywords: Diabetic nephropathy, urea, creatinine, Syzygium aqueum